Switch from Immediate-release Pramipexole to Extended-release Pramipexole: The Safety and Efficacy Characteristics of Sixty-eight Patients - Müge Kuzu; İnci Şule Özer; Oğuzhan Herdi; Sabiha Tezcan; Muhittin Cenk Akbostancı (Türk Nöroloji Dergisi, 2016)
Objective: To evaluate the safety and efficacy of switching from immediate-release pramipexole (pex) to extended-release pramipexole (pex-ER). Materials and Methods: Pex-ER became available in Turkey about a year ago, since then we documented satisfactory information on patients (26 women; 38%) who were switched from pex to pex-ER. We recorded pre- and post-switch pex and levodopa, equivalent doses of other anti-parkinsonian medication, and analyzed the frequency and nature of reported adverse effects. Results: The mean age of the patients was 63.3 years (range, 44-88 years), and the mean disease duration was 7.1 years (range, 1-27 years). The other drugs were levodopa (57 patients, 82.6%), entacapone (24 patients, 34.58%), rasagiline (20 patients, 29%), amantadine (18 patients, 26.1%), and apomorphine (six patients, 8.7%). Switch from pex to pex-ER was uneventful in 62 (91.2%) patients. Adverse events were reported in six (8.8%) patients: ankle swelling (two patients), nausea (one patient), dyskinesia (one patient), hypersexuality (one patient), and psychosis (one patient). Problems resolved with further medication change in two patients. Four patients preferred to return to pex. Conclusion: The great majority of patients (91.2%) switched from three times daily pex to once daily pex-ER uneventfully. A slight increase in pex daily dose, which was tailored according to patients’ symptomatic needs, resulted in an increase in post-switch levodopa equivalent doses. Our experience is compatible with previously reported studies.